2004
DOI: 10.1055/s-2004-813279
|View full text |Cite
|
Sign up to set email alerts
|

MR Elastography of the Prostate: Initial In-vivo Application

Abstract: In-vivo MRE of the prostate gland is technically feasible. The proposed experimental set-up allows the efficient insertion of the mechanical wave into the prostate gland and provides a successful MR data acquisition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 14 publications
5
104
0
1
Order By: Relevance
“…MRE measurements indicated that the peripheral portion of the prostate was stiffer than the central portion. The mean Young's modulus values were 9.9 kPa and 6.6 kPa, respectively (Kemper et al 2004). Significant discrepancies were also found on the reported stiffness of kidney tissue (Erkamp et al 1998;Kruse et al 2000;Nasseri et al 2002;Snedeker et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRE measurements indicated that the peripheral portion of the prostate was stiffer than the central portion. The mean Young's modulus values were 9.9 kPa and 6.6 kPa, respectively (Kemper et al 2004). Significant discrepancies were also found on the reported stiffness of kidney tissue (Erkamp et al 1998;Kruse et al 2000;Nasseri et al 2002;Snedeker et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of dynamic MRE clinical implementation has been proven in preliminary human studies in which the data of human prostate, breast, brain, muscle, and liver were presented (Bensamoun et al 2006;Bishop et al 1998;Kemper et al 2004;Kruse et al 2000;Papazoglou et al 2006;Rouviere et al 2006;Sinkus et al 2005). In particular, Kruse et al (2000) evaluated porcine livers with MRE at multiple shear wave frequencies and reported that the wave velocity and the shear stiffness increased with frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Previously MRE has been successfully applied to the study of the mechanical properties of a variety of other organs and soft tissue regions in vivo, including the breast, brain, kidney, prostate, liver, and muscle. [16][17][18][19][20] Application to the lungs has proven more challenging given the poor signal-to-noise available in imaging due to a lower presence of hydrogen in air than in soft tissue (containing water) and the complex nature of vibratory wave propagation found in the lungs. A better understanding of mechanical wave motion in the lungs would aid in the interpretation of the wave images that are acquired using MRE to reconstruct a quantitative map of variation in mechanical properties that can correlate with injury, the progression of disease, and/or the response to therapy.…”
Section: Introduction a Motivationmentioning
confidence: 99%
“…Elastography has opened new possibilities to determine elasticity. Recently, Kemper et al [9] published elasticity coefficients for the prostate. We have also performed another parallel study concerning the ability to translate FEM parameters (Young modulus for instance) in a local shape memory force.…”
Section: Discussionmentioning
confidence: 99%